2020
DOI: 10.3324/haematol.2019.242974
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab inhibits acute myeloid leukaemia metabolic capacity by blocking mitochondrial transfer from mesenchymal stromal cells

Abstract: inhibits acute myeloid leukaemia metabolic capacity by blocking mitochondrial transfer from mesenchymal stromal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Acute myeloid leukemia (AML) is another disease where the anti-tumor effects of DARA have been investigated. In combination with all-trans retinoic acid (ATRA), DARA enhanced cytotoxicity of AML cells [ 70 ], while as a single agent, DARA induced an inhibition of mitochondrial transfer from mesenchymal stromal cells to AML cells, thus reducing the tumor burden [ 71 ]. Moreover, the efficacy of anti-CD38 therapy was assessed also in post-transplant refractory B-acute lymphoblastic leukemia [ 72 , 73 , 74 ].…”
Section: Clinical Applications Outside MMmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is another disease where the anti-tumor effects of DARA have been investigated. In combination with all-trans retinoic acid (ATRA), DARA enhanced cytotoxicity of AML cells [ 70 ], while as a single agent, DARA induced an inhibition of mitochondrial transfer from mesenchymal stromal cells to AML cells, thus reducing the tumor burden [ 71 ]. Moreover, the efficacy of anti-CD38 therapy was assessed also in post-transplant refractory B-acute lymphoblastic leukemia [ 72 , 73 , 74 ].…”
Section: Clinical Applications Outside MMmentioning
confidence: 99%
“…A new study indicated that daratumumab, an anti-CD38 monoclonal antibody, could inhibit AML disease progression via a mechanism involving blocking mitochondrial transfer from MSCs to AML blasts. 176 As malignant tumors develop as part of a high-metabolic and invasive complex, future studies are required to investigate the profound effect of mitochondrial acquisition on the respiratory metabolism of cancer cells and to explore a valid approach for the inhibition of mitochondrial transfer in the TME with minimal side effects.…”
Section: Perspectives and Applicationsmentioning
confidence: 99%
“…The surface molecule CD38 is critical for the transport of mitochondria from MSCs to AML cells [ 127 ]. Daratumumab, a monoclonal anti-CD38 antibody approved for the treatment of multiple myeloma, was shown to block the delivery of mitochondria to AML cells, decrease the oxygen consumption rate, and inhibit the growth of leukemic cells [ 128 , 129 ]. Main regulators of mitochondrial biogenesis and activity including PGC-1α and NOX2 are also promising targets.…”
Section: Combinatorial Strategies To Overcome Aml Resistance To Immunotherapymentioning
confidence: 99%